Potential Use of Nanomedicine for the Anti-inflammatory Treatment of Neurodegenerative Diseases - Cayero-Otero, Maria D.; Espinosa-Oliva, Ana M.; Herrera, Antonio J.; Garcia-Dominguez, Irene; Fernandez-Arevalo, Mercedes; Martin-Banderas, Lucia; de Pablos, Rocio M. (Current Pharmaceutical Design, 2018)
Neurodegenerative diseases, like Alzheimer´s and Parkinson´s disease, are a group of disorders that have in common their increasingly high prevalence along with the shortage of effective treatments. In addition, the scientific community faces the challenge of getting the drugs used in these treatments to cross the blood-brain barrier (BBB) and reach the brain in sufficient concentration to be able to exert its effect. Hence, researchers across multiple disciplines are working together in order to improve the ability of therapeutics to penetrate the BBB. In this sense, the use of nanomedicine, nanoscale structures for drug delivery, exhibits a really high therapeutic potential in the field of neurodegenerative diseases therapy. Since there is new evidence that neuroinflammation produced by reactive microglia contributes to the activation and pathogenesis of neurological disorders, many investigations focus on the identification of new targets whose inhibition can reduce, totally or partially, microglial activation. This review analyzes a wide variety of compounds as possible candidates to achieve this target, from compounds with a natural origin to anti-diabetics, antidepressants, antibiotics and hormones. We also discuss the different strategies to enhance the capacity of these compounds to cross the BBB. Although this review focuses on PLGA nanoparticles as one of the most versatile drug delivery nanosystems, we also describe other strategies, such as direct intranasal administration (nose-tobrain), novel viral vectors and novel implanted catheters.
Keywords: Parkinson´s disease